PROPAGASI PADA VARIETAS TANAMAN YANG DILINDUNGI BERDASARKAN UNDANG-UNDANG NOMOR 29 TAHUN 2000 TENTANG PERLINDUNGAN VARIETAS TANAMAN - Irawan, Vania (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The topic of this research is Plant Breeder’s Right or PBR with the purpose to find out and analyze propagation. This research will discuss and analyze the 1991 UPOV Convention relating to propagation. In addition, it will also discuss about farmers as one of parties who carry out propagation and about propagation’s infringement. This topic deserve to be discussed because there are many issues regarding PBR in Indonesia with few articles that discuss about it, especially in the legal field. The method used in this research is normative with a statute approach.